PURCHASE BINDING AGREEMENT FOR PARTIES (PURCHASER AND DEVELOPER) - Rosnidar Sembiring (USU Journal of Legal Studies, 2017)
Purchase Binding Agreement on housing is a preliminary agreement between a seller and a potential buyer as it is stipulated in Article 42, paragraph 1 of Law No. 1/2011 on Housing and Residence and in Kemenpera (the Decree of the Minister of Low-Cost Housing) No. 9/1995 which become the basis for PPJB as the preliminary agreement. Even though PPJB is consensual, it is made by paying attention to good faith principle as it is stipulated in Article 1338, paragraph 3 of the Civil Code. this thesis attempted to analyze the legal consequence of PPJB. The research used judicial normative (doctrinal) with descriptive analytic and explanatory method. The result of the research showed that the legal consequence of PPJB was binding for the parties concerned and the legal ground of PPJB was Law No. 1/2011 on Housing and Residence, Kemenpera No. 9/1995 on the Guidance for Purchase Contract, and Article 1338, paragraph 1 of the Civil Code.